1985
DOI: 10.1002/jobm.3620250821
|View full text |Cite
|
Sign up to set email alerts
|

Detection of two ornithine carbamoyltransferases in a phaseolotoxin‐producing strain of Pseudomonas syringae pv. phaseolicola

Abstract: The phaseolotoxin-producing Pseudomonas syringae pv. phaseolicola strain 1321 contains two ornithine carbamoyltransferases which differ in resistance to phaseolotoxin. Whereas ornithine carbamoyltransferase 1 (OCT 1) is inhibited at low concentrations of phaseolotoxin, ornithine carbamoyltransferase 2 (OCT 2) is insensitive to phaseolotoxin. The activity of the insensitive enzyme is correlated with the amount of toxin formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…First, increase in temperature from 21 to 28°C caused a 28% decrease in the level of PhoA. This reduction was smaller in magnitude than previously reported for ROCT activity caused by elevated temperature (73% from 22 to 30°C [33]). Although reporter protein activity is not a direct measure of transcription, it is possible that the amplitude of temperature regulation differs between strains.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…First, increase in temperature from 21 to 28°C caused a 28% decrease in the level of PhoA. This reduction was smaller in magnitude than previously reported for ROCT activity caused by elevated temperature (73% from 22 to 30°C [33]). Although reporter protein activity is not a direct measure of transcription, it is possible that the amplitude of temperature regulation differs between strains.…”
Section: Discussionmentioning
confidence: 57%
“…phaseolicola (19,33,79,82) showed that growth temperature modulates the level of ROCT specific activity, which decreases as the growth temperature is raised from 18 to 30'C. Templeton et al (83) further showed that arginine, which causes repression of anabolic OCTs in most microorganisms, did not have a significant effect on the specific activity of ROCT from P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, P. syringae pv. phaseolicola is insensitive to the effect of its own toxin due to the presence of a phaseolotoxinresistant OCTase (7,37), which is produced under conditions leading to the synthesis of phaseolotoxin (13,14) and is encoded by the argK gene (10,26).…”
mentioning
confidence: 99%
“…To protect itself from its own toxin, P. syringae pv. phaseolicola synthesizes a phaseolotoxin-resistant OCTase (ROCT) (6,10,11,25,34).…”
mentioning
confidence: 99%